Future Prospects in Balanced Scorecard Research: Sustainability Perspective - Mehtap Aldogan Eklund (Indonesian Journal of Sustainability Accounting and Management, 2020)
This paper reviews the state of the research on a balanced scorecard (BSC) and sustainability balanced scorecard (SBSC) from 1990 to 2020. It aims to address the research question, "What are the future prospects in the BSC research from the perspective of sustainability?” using an integrative literature review method with bibliometric analysis. This study also reports the evolution and synthesis of published materials, citation analysis, themes, theories, and the literature gap and future research agenda, including the post coronavirus disease 2019 (COVID-19) sustainability crisis. The findings of this study, which aim to advance the knowledge in the field, include the developed future research framework matrix and the proposed research questions regarding the research gap in the multi-dimensional, multi-disciplinary, and multi-cultural empirical research. This study is considered unique owing to its comprehensive, holistic, and up-to-date structure. Furthermore, such a research design facilitates interdisciplinary, theory-driven research with the review in multiple disciplines, which is new to the accounting literature. One limitation of this study is that it is a conceptual study; however, it can pave the way for future empirical and mixed-method studies in this field.